Trends and Effectiveness of Indonesian Language Learning Models: A Systematic Literature Review (SLR) - Muhammad Binur Huda; Dani Dwi Saputra; Roby Muhammad Mahib (Journal of Science and Education (JSE), 2026)
Indonesian language learning has a strategic role in developing literacy skills, critical thinking skills, and communicative skills of students at various levels of education. Curriculum changes, technological developments, and 21st-century skills need demand more varied, innovative, and adaptive learning models. However, previous research has shown that the use of learning mod-els in the classroom is still not optimal, while teachers need empirical refer-ences regarding effective learning models. This study aims to map the trends and effectiveness of various Indonesian language learning models through the Systematic Literature Review (SLR) approach. The research method fol-lowed the PRISMA protocol by analyzing 24 selected articles from national and international databases. The results of the analysis showed that con-structivism-based models such as Problem-Based Learning, Project-Based Learning, Discovery Learning, and Cooperative Learning more consistently improved the ability to read, write, speak, and think critically. In addition, learning trends show a shift towards a collaborative and integrative approach that is relevant to the Independent Curriculum. The discussion emphasized that the effectiveness of each model is greatly influenced by the learning context, student characteristics, and digital media support. This research contributes in the form of comprehensive mapping to assist teachers and re-searchers in determining learning strategies that are more effective and re-sponsive to the needs of Indonesian language learning